In vitro bud proliferation response in ivy gourd (Coccinia grandis (L.) Voigt.) cv. Sulabha nodal explants with cytokinin levels - Thasni, A.; Sarada, S.; Alex, Swapna (Journal of Tropical Agriculture, 2023)
MS medium supplemented with different concentrations of cytokinins, Kn (0.1-1.0 mg L-1) and BA (0.1-1.0 mg L-1), individually and in combination was used to study the bud proliferation and shoot induction responses in ivy gourd. The combination MS + 1.0 mg L-1 BA was the best with respect to the number of days for bud initiation (5.50), number of shoots per explant (1.75), shoot length (5.71) and percentage of response (100).The micro shoots obtained from the best medium (MS+BA1mg L-1) have successfully produced shoots in MS + BA 1 mg L-1 + IBA 0.3 mg L-1 and rooted in MS+BA 1mg L-1+IBA0.2 mg L-1.